(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate obesogenic lifestyle and nutritional habits in a single study including a large population of children.Materials and Methods: A cross-sectional study was conducted with children aged between 6-12 years from 5 primary schools (n = 1002) in Istanbul, Turkey between April–June 2019. A questionnaire was filled which included information about weight, height, sleep duration, daily screen time and eating habits.Results: It was observed that obese children had significantly shorter sleep duration compared to children in other body mass index (BMI) groups (p = 0.001). It was found that median age was higher in children who slept less than 9 hours compared to those who slept 9 hours or more (p = 0.001). We also found that the median daily screen time of children who slept less than 9 hours was higher than the rest (p = 0.024).Conclusion: There was a significant relationship between short sleep duration and overweight / obesity prevalence and increased daily screen time. Sleep duration can be a potentially modifiable risk factor in the prevention and treatment of childhood obesity.